THE IMPACT OF THE MISREPRESENTATION OF JIHAD ON THE INTEGRATION OF A MULTI-FAITH SOCIETY - Bayan Omar Alshabani (PalArch's Journal of Archaeology of Egypt / Egyptology, 2021)
Misrepresented discourse presents Muslims as people whose purpose in life is to harm non-Muslims and to target them with violence. And that their legal discourse legitimises the use of force for that purpose. This paper uses social psychology as to examine the impact of the misrepresentation of jihad on the social level especially the social dynamics in a multi-faith society after terror attacks. This has participated in creating the cognitive aspect of prejudice against Islam and Muslims, and that terror attacks which target multi-faith societies stimulate prejudice against the Muslim population of that particular society. It is particularly dangerous, as these misrepresentations have been normalised in the discourse. This paper has analysed the impact of misrepresentation and how it affects the integration of a multi-faith society. This work was done using performativity in Speech Act theory, social psychology , schema theory and framing theory. This paper has discussed that misrepresented discourse creates the cognitive aspect of prejudice by confusing a legal term (jihad) in Islamic International law with criminal act (terrorism), normalising misrepresentation and categorising Muslims as out-group members who pose a threat to the in-group. For that reason, terror attacks targeting a multi-faith society are the stimulus that activates prejudicial acts against the Muslim population. This paper has also asserted that misrepresentation causes the domination of radical ideology and demonises the role of legal discourse and counter-terrorism policies because misrepresented discourse uses the performative of "jihad" as it occurs in radical discourse and it effects the integration in the in a multi-faith society.